1974
DOI: 10.1507/endocrj1954.21.9
|View full text |Cite
|
Sign up to set email alerts
|

Blockade of Spontaneous Ovulation by Isocarboxazid (MAO-Inhibitor) in Rats

Abstract: SynopsisSpontaneous ovulation was inhibited in female rats with isocarboxazid (IC), MAO-Inhibitor. Administration of HCG to IC-treated females at 3:00p.m. on the day of proestrus induced ovulation. Although the brain serotonin level was still high (1.5 times the control) from 9:00a m. to 6:00p.m. on the next day after IC-injection, ovulation occurred on the second day morning. Female rats, with the increased brain serotonin level by IC-injection, copulated on the afternoon of proestrus, and ovulation occurred … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

1979
1979
2008
2008

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 5 publications
0
1
0
Order By: Relevance
“…Early pharmacological studies have sug gested that a serotonergic mechanism can in hibit ovulatory LH release [3,15,17,29,30,32,34,42,44,54], More recent studies em ploying similar pharmacological procedures, have suggested that a facilitatory serotonergic mechanism also plays a role in regulating the LH surge [9,23,25,26,35,53], Meyer [36], utilizing microinjection of neurotoxin directly into the raphe area, has implicated raphehypothalamic serotonergic projections in this facilitatory effect. On the basis of the results of the present paper, we can conclude that no data yet available convincingly demonstrate an involvement of raphe neurons in the in hibitory mechanism.…”
Section: Discussionmentioning
confidence: 99%
“…Early pharmacological studies have sug gested that a serotonergic mechanism can in hibit ovulatory LH release [3,15,17,29,30,32,34,42,44,54], More recent studies em ploying similar pharmacological procedures, have suggested that a facilitatory serotonergic mechanism also plays a role in regulating the LH surge [9,23,25,26,35,53], Meyer [36], utilizing microinjection of neurotoxin directly into the raphe area, has implicated raphehypothalamic serotonergic projections in this facilitatory effect. On the basis of the results of the present paper, we can conclude that no data yet available convincingly demonstrate an involvement of raphe neurons in the in hibitory mechanism.…”
Section: Discussionmentioning
confidence: 99%